Laparoscopic versus open appendectomy in complicated appendicitis in children: a single center study - Mohammad Seqsaqa; Ahmed Ezzat Rozeik; Mohammed Khalifa; Hazem Nour Abdellatif Ashri (SpringerOpen, 2020)
Abstract Background Acute complicated appendicitis is a common abdominal emergency in children. Unlike simple appendicitis, laparoscopic appendectomy has not been considered yet the first choice in management of complicated appendicitis. This prospective randomized controlled clinical trial was conducted at Pediatric Surgery Department, Zagazig University Hospitals, Egypt, during the period from December 2018 to August 2019. The aim of the study was to evaluate the role of laparoscopic appendectomy in such cases compared to open appendectomy. Results Sixty patients were included in the study, divided randomly into 2 equal groups: laparoscopic and open appendectomy groups. The mean operative time was significantly longer with laparoscopic appendectomy than open appendectomy, 85 vs. 61 min, respectively (p < 0.001**). The time taken to start oral intake was significantly shorter with laparoscopic appendectomy than open appendectomy, 1.9 vs. 2.73 days, respectively (p = 0.025*). The mean hospital stay was significantly lower with laparoscopic appendectomy than open appendectomy, 4.23 vs. 5.13, respectively (p = 0.044*). There were no statistical differences between the two groups regarding wound infection, occurrence of postoperative ileus, intraperitoneal collection, or readmission. Conclusions Laparoscopic appendectomy is safe, feasible, and effective procedure in the management of complicated appendicitis in children, with no evidence of any increase in the postoperative complications.